External Finance and Foreign Debt in Central and Eastern European Countries - Manzocchi, Stefano (IMF Working Papers; Working Paper ;, 1997)
External finance can provide a positive contribution to the transition process and can enhance welfare in former centrally planned economies, especially when domestic saving has not fully recovered after the initial contraction. However, as was pointed out at the beginning of the transition process, foreign debt could exert a strong constraint on the borrowing capacity of some central and eastern European countries. This paper analyzes the determinants of net external borrowing in ten transition economies during 1990-95 and assesses the impact of the outstanding stock of foreign liabilities on net financial inflows.